POTENSI PENGEMBANGAN USAHA PENGOLAHAN BAWANG GORENG LOKAL DI KOTA PALU - Chitra Anggriani Salingkat (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
The research aims were to: (1) identify the production of local fried shallot, (2) determine the market demand of local fried shallot, and (3) identify supply continuity of fried shallot commodity.  The population of the research was ten small – medium fried shallotbusinesses (UKM) in Palu city.  Samples selected were based on a Purposive Sampling technique.  Data recorded was analyzed using descriptive analysis and one way t-test.  The results showed that the total amount of fried shallot demand was 30.730 kg and the total amount of fried shallotproduction was 18.360 kg in Palu city.  The demand for the fried shallot was significantly ( larger than its production suggesting that there is a big potency for UKM to be developed. Keywords :, Fried onion, Market demand, Potency, Processing, Production.